Therapeutic roles of polysaccharides from Dendrobium Officinaleon colitis and its underlying mechanisms. (1st April 2018) - Liang, Jian; Chen, Shuxian; Chen, Jianhui; Lin, Jizong; Xiong, Qingping; Yang, Yiqi; Yuan, Jun; Zhou, Lian; He, Lian; Hou, Shaozhen; Li, Shijie; Huang, Song; et al.
Highlights: Polysaccharides from Dendrobium officinal (DOPS) could attenuate ulcerative colitis. Its mechanism on anti-colitis involved inhibition of NLPR3 inflammasome activation. Its mechanism on anti-colitis involved suppression of β-arrestin1 signaling pathways. Abstract: Polysaccharide, as a promising candidate to meet the medication requirement of ulcerative colitis (UC), is increasingly attracting extensive interest. Dendrobium officinale has been widely used to treat gastrointestinal sickness in the clinical treatment of Traditional Chinese Medicine. However, it remains largely unknown whether polysaccharides (DOPS) from Dendrobium officinale can treat UC. The purpose of this paper is to confirm therapeutic action of DOPS to UC and explored its underlying mechanisms. We noted that DOPS could dramatically improve clinical signs and symptoms, decrease mortality, alleviate colonic pathological damage, and reestablish the balance of pro- and anti-inflammatory cytokines in DSS-induced acute UC mice. Moreover, DOPS treatment could also markedly suppress the activation of NLRP3 inflammasome and β-arrestin1 in vivo and in vitro . This study showed that DOPS possesses appreciable therapeutic effect to treat experimental acute UC mice. Its mechanism could be related to inhibition of NLRP3 inflammasome and β-arrestin1 signaling pathways.